The effects of induction motor's steel sheet thickness on efficiency, losses and electrical cost - Yahya Y.B.; Rahmat M.K.; Salleh S.F.; Abdullah T.A.R.B.T. (Penerbit UTHM, 2023)
Application of the induction motor in industry is common transversely the world. Performance evaluation of its energy efficient was increased the attention as it will convey important energy and commercial funds. This research considered the effects of electrical steel sheet's thickness for rotor material of 0.5Hp 3-phase induction motor on energy efficiency, losses reductions and utility bill cost. The outcome for this research work is thru reducing the lamination thickness of steel sheet (from 0.50 mm to 0.35 mm) for rotor frame, the energy efficiency was increased by 1.4% and 13.27Watt of losses have been decreased. Uncertainty the new design is applied to 100, 000 pieces a new rotor of motor, it is assessed that 40.32kWh/year of energy might be saved also the utility bill will be saved up to RM 1.35million. Universiti Tun Hussein Onn Malaysia Publisher's Office.